Annual rings in a native Hawaiian tree, Sophora chrysophylla, on Maunakea, Hawaiʻi. (12th August 2015) - Francisco, Kainana S.; Hart, Patrick J.; Li, Jinbao; Cook, Edward R.; Baker, Patrick J.
Abstract: Annual rings are not commonly produced in tropical trees because they grow in a relatively aseasonal environment. However, in the subalpine zones of Hawaiʻi's highest volcanoes, there is often strong seasonal variability in temperature and rainfall. Using classical dendrochronological methods, annual growth rings were shown to occur in Sophora chrysophylla, a native tree species on Maunakea, Hawaiʻi. Chronologies were established from nearby non-native, live conifer trees and these were used to verify the dates from a total of 52 series from 22 S. chrysophylla trees, establishing an 86-y chronology (1926–2011). Ring-width patterns were significantly correlated with monthly rainfall from August of the previous year. This study is the first in the eastern tropical Pacific region to demonstrate annual growth rings in trees.